- Implementation of Project Based Learning Model in Vocational High School: A systematic Literature Review - Suparmi Suparmi; Fatma Sukmawati; Budi Tri Cahyono; Eka Budhi Santoso; Relly Prihatin; Ratna Juwita (Postgraduate, University of Mataram, 2024)
This research aims to provide a comprehensive overview of the implementation of project-based learning in Vocational High Schools (VHS). The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) was used as the method. The research results show that first, PjBL in Indonesia vocational high schools and abroad has an impact on student interest and motivation also students' learning outcomes in various aspects; second, the flexibility of the model consists of time in the classroom and time outside the classroom; third, teacher’s main roles are design the instruction, media selected, and facilitate students in learning with measuring the extent of students' understanding; fourth, model, media, and strategies, there are various activities can be integrated into Project Based Learning; Fifth, Model can be applied in various vocational fields. Benefits, challenges, and recommendations for further research are also provided.